Analysis of factors affecting audit delay in manufacturing and financial companies listed on IDX - Muna, Eristamia Faizul; Lisiantara, G. Anggana (Indonesia Accounting Journal, 2021)
The study aims to identify and analyze the factors affecting the audit delay. The study includes a quantitative study using secondary data obtained from the company’s financial statement. The study’s population constituted the entire manufacturing and finance companies listed on the Indonesia Stock Exchange during the year 2018-2019. The sample is collected by using purposive sampling over the listed companies in the criteria that the company publishes the audited financial report as of December 31 and also shows the data needed in the study. The sample which has met the criteria is 510 companies and analyzed by multiple linear regression analysis. The results show that the industrial type and complexity of the company have a positive influence on the audit delay, the auditor opinions, the reputation of Public Accounting Firm and the company’s size have a negative impact on the audit delay, while the profitability does not affect the audit delay.